Predicting the air quality, thermal comfort and draught risk for a virtual classroom with desk-type personalized ventilation systems - Conceição, Eusébio (2018)
This paper concerns the prediction of indoor air quality (IAQ), thermal comfort (TC) and draught risk (DR) for a virtual classroom with desk-type personalized ventilation system (PVS). This numerical study considers a coupling of the computational fluid dynamics (CFD), human thermal comfort (HTC) and building thermal behavior (BTB) numerical models. The following indexes are used: the predicted percentage of dissatisfied people (PPD) index is used for the evaluation of the TC level; the carbon dioxide (CO2) concentration in the breathing zone is used for the calculation of IAQ; and the DR level around the occupants is used for the evaluation of the discomfort due to draught. The air distribution index (ADI), based in the TC level, the IAQ level, the effectiveness for heat removal and the effectiveness for contaminant removal, is used for evaluating the performance of the personalized air distribution system. The numerical simulation is made for a virtual classroom with six desks. Each desk is equipped with one PVS with two air terminal devices located overhead and two air terminal devices located below the desktop. In one numerical simulation six occupants are used, while in another simulation twelve occupants are considered. For each numerical simulation an air supply temperature of 20 degrees C and 24 degrees C is applied. The results obtained show that the ADI value is higher for twelve persons than for six persons in the classroom and it is higher for an inlet air temperature of 20 degrees C than for an inlet air temperature of 24 degrees C. In future works, more combinations of upper and lower air terminal devices located around the body area and more combinations of occupants located in the desks will be analyzed.